Analysis of opacification patterns in intraocular lenses (IOL). Issue 1 (11th February 2021) - Mackert, Marc; Muth, Daniel Rudolf; Vounotrypidis, Efstathios; Deger, Constanze; Goldblum, David; Shajari, Mehdi; Hasler, Pascal Willy; Priglinger, Siegfried; Wolf, Armin
Abstract : Objective: Intraocular lens (IOL) opacification may cause severe visual impairment. The pathogenesis remains unclear. The aim of this study was to analyse opacification patterns in different IOLs. Therefore, this multicentre, retrospective, observational study was conducted at Ludwig-Maximilians-University, Munich, Germany and University-Hospital Basel, Switzerland. Methods and analysis: In this study, 75 opacified IOLs were identified and classified after extraction. Macroscopical photo documentation, light and electron microscopic analysis were done. Results: 68 acrylic-hydrophilic single-piece-IOLs, 1 acrylic-hydrophilic 3-piece-IOL, 6 acrylic-hydrophobic 3-piece-IOLs were extracted. The dataset comprised IOLs known for opacification and IOLs not having been reported yet. 67 IOLs showed a fine-granular and 8 IOLs a crust-like opacification pattern. According to literature, 62 of the fine-granular opacified IOLs were graded into type 1 (processing/packaging-induced primary opacification) and 13 into type 2 (secondary opacification of unknown aetiology). The anterior surface of the IOLs was affected in all 75 IOLs, the posterior surface only in 23 cases. Of all 67 fine-granular IOLs, 43 had a central defect and 21 had a zone without opacification (clear islet). Conclusion: In our series, the morphology of IOL opacification did not follow the existing pathogenetic classification that strictly discriminates between primary and secondary causes. Fine-granular IOL opacification occurs with similar patterns in both type 1 and type 2 IOL opacification, while a crust-like pattern was only detected in type 2 IOL opacifications. Consequently, susceptibility of an IOL to opacification is caused by a multifactorial combination of material and processing properties as well as individual (pathological) conditions of the patient.